Designing mine tailings for better environmental, social and economic outcomes: A review of alternative approaches - Edraki, M.; Baumgartl, T.; Manlapig, E.; Bradshaw, D.; Franks, D.; Moran, Chris (Elsevier, 2014)
© 2014 Elsevier Ltd. All rights reserved.With the unprecedented rate of mining and mineral processing over the past decade, there has been an increasing level of concern worldwide about the fate of tailings and the irreversible consequences of contaminant release through dust, tailings dam seepage, dam wall failure, or direct disposal of tailings into waterways. It is likely that in the future the mining of higher tonnages of lower grade ore and the possibility of more extreme weather events associated with global climatic change, may increase the risks associated with mine tailings management. In this paper we review alternative tailings management methods that aim to improve environmental, social and economic outcomes. Three approaches in particular are highlighted: paste and thickened tailings; tailings reuse, recycling and reprocessing; and proactive management (e.g. The integration of sulphide flotation with cemented paste backfill). The aim of the present study is to scope the opportunities that could be gained by developing an integrated research framework that traces tailings properties back to the orebody. In the future models could be constructed to optimise environmental, social and economic outcomes of tailings management across the value chain through integrated orebody characterisation, mine planning, processing, disposal, reprocessing, recycling and reuse.